The annual effective dose for children resulting from the ingestion of radioactive nuclides found in basic diets - Kadhim, Inaam H.; Alghazaly, Saif M.; Al-Sadi, Mohammed Abdul Kadhim Hadi (International Journal of Innovative Research and Scientific Studies, 2025)
The concentrations of natural radionuclides uranium-238 (238U), thorium-232 (232Th), and potassium-40 (40K) were determined in sixteen basic baby meals that were randomly collected from the markets of Hilla, Iraq, using NaI(Tl). The activity concentration of 238U ranged from 0.075 ± 0.013 Bq.kg-1 in (MG1) to 18.21 ± 0.055 Bq.kg-1 in (SG2), with an average value of 4.00 ± 0.145 Bq.kg-1. The concentration of 232Th ranged from 0.067 ± 0.009 Bq.kg-1 in (MG4) to 15.60 ± 0.08 Bq.kg-1 in (FG1), with an average of 4.97 ± 0.149 Bq.kg-1, while the 40K concentration ranged from 7.210 ± 1.932 Bq.kg-1 in (FG4) to 321.75 ± 0.89 Bq.kg-1 in (MG2), with an average of 96.384 ± 0.895 Bq.kg-1. The annual effective dose resulting from radionuclide ingestion was calculated by analyzing the spectrum of radionuclides and using the annual rate of food consumption and age-dependent dose conversion parameters published in the report of the United Nations Scientific Committee on the Effects of Atomic Radiation. The total effective dose ranged from 0.930 μSv.y-1 in (MG1) to 0.197 μSv.y-1 in (SG2), with an average value of 55.188 μSv.y-1, all of these values being less than the global total dose value of 200 μSv.y-1 for all. This study could be helpful because updated data show a database of natural radionuclide activity in some children’s staple diets and annual effective exposure dose values.